Strategic Planning Information Systems Enterprise Architecture Planning Method Case Study of Semarang City Public Works Department - Agustinus Fritz Wijaya; Mahendra Wahyu Prasetyo (Journal of Information System and Informatics, 2020)
Semarang City Public Works Department is a state-owned enterprise that works in the area of public services in the city of Semarang. Most of the technological conditions in the Public Works Department are still in manual data management, which is hampering business processes from going well. Therefore this research was conducted to design an Information System at the Semarang City Public Works Department using the Enterprise Architecture Planning (EAP) method which includes a SWOT analysis and Value Chain analysis. The existing framework in the Enterprise Architecture Planning (EAP) method can help align the data architecture and application architecture to get the expected results, which is achieving the business objectives of the City of Semarang Public Works Department so that business functions can run by the desired business processes. This research resulted in several proposals for the development of Information Systems and Information Technology in organizations including the development of several applications in the next 5 years.